Hypothetical Learning Trajectory Berbasis Realistics Mathematics Education - Maria Magdalena Zagoto; I Made Arnawa; Edwin Musdi; Firman Edi; Oskah Dakhi; Unung Verawardina (Edumaspul: Jurnal Pendidikan, 2022)
The purpose of this research was to produce a Hypothetical Learning Trajectory (HLT) for the addition of fractions with the same denominator using the context of löma typical food of Nias region. The learning approach used was Realistics Mathematics Education (RME). The research method used was design research. The research subjects were three fourth grade students of SDN 071104 Botohilitano with heterogeneous ability levels, namely low, medium and high ability. The research focused on designing HLT which was validated, revised and tested one-to-one with students. Data collection was carried out by collecting the results of the NLPD given, and interviewing students. Retrospective analysis of the one to one implementation showed that the context of the instrument used in the form of HLT and learner worksheets using the RME approach through literature study. The data collected was analyzed qualitatively. Based on the results of the analysis, it was found that students with medium and high abilities could understand the material quite well, while low ability students had difficulty in understanding the problems given.